Cold storage for fruit and vegetables - Kessler, John Martin (My University, 1899)
Introduction: It is less than a hundred years ago since men found ice valuable enough as a preservative to be shipped to southern lands. Indeed, the users of ice were very few, and it was not until about the middle of this century that men discovered its many possibilities. At present, it may be said that nearly every inhabitant of this country gets some benefit either directly or indirectly from the many uses of ice. It is estimated that at present there is a capital of from forty to fifty millions of dollars invested in this industry. The idea of storage for fruit and vegetables, as well as other products, is a natural outgrowth of our improved methods of production or/and outgrowth of the so called “over production” if there be such an evil. Storage was brought about by; first, over stacked markets, which are of short duration, second, short seasons that certain fruits, as peaches, can endure, and third, entire crop failure.
Citation: Kessler, John Martin. Cold storage for fruit and vegetables. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Cold Storage; Machinery for Making Artificial Ice; Length of Time of Preservation; Theses; Manuscripts (documents)